An energy analysis during forging of sintered truncated conical preform at high speed - Singh S.; Jha A.K.; Kumar S. (My University, 2025)
The upper bound method though an approximate energy method to obtain exact mathematical solutions is still preferred for analysis of metal forming problems. Although much work has been reported on the analysis of sinter-forging of preforms with simple generic shapes such as solid cylindrical discs and rectangular strips, the analysis of sinter-forging of truncated conical preform has not been considered. The present work deals with the upper bound analysis of axi-symmetric high-speed sinter-forging of truncated conical preforms under cold conditions by accounting for an exponential velocity field taking bulging and inertia effects. A generalized expression for average forging load has been established and the effect of taper angle, preform height and interfacial friction conditions at die-workpiece interface during deformation has been critically studied.